The Phonological Development of Mandarin Voiceless Affricates in Three- to Five-Year-Old Children - Ma, Junzhou; Wu, Yezhou; Zhu, Jiaqiang; Chen, Xiaoxiang (Frontiers in Psychology, 2022)
This study investigates the phonological development of Mandarin voiceless affricates produced by Mandarin-speaking children. Thirty-six monolingual Mandarin-speaking children and twelve adults participated in a speech production task. Auditory-based transcription analysis and acoustic analysis were utilized to quantify the relative order of affricate acquisition. Both methods yielded earlier acquisition of alveopalatal affricates at age three than retroflex and alveolar affricates, whereas they differed in the acquisition order of retroflex and alveolar affricates. The former revealed that both retroflex and alveolar affricates were acquired at age five, regardless of aspiration, while the latter yielded earlier acquisition of retroflex than alveolar affricates. Possible reasons for the discrepancy are discussed in relation to the different nature of the two methods. Overall, the observed acquisition order of Mandarin voiceless affricates suggests that child speech development is a complex process, and is influenced by various factors including oromotor maturation and language-specific phoneme frequencies in the ambient language.